Population genetic parameters and breeding values of reproduction and nursing traits in Hungarian Large White pig - Bene, Szabolcs; Fekete, Zsuzsanna; Lendvay, Miklós; Rajnai, Csaba; Polgár, Péter J.; Szabó, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
Some population genetic parameters of reproduction and nursing traits were evaluated in the seedstock Hungarian Large White herd of the University of Pannonia Georgikon Faculty at Keszthely. Data of 64 breeding boars mated to 1000 sows resulting 4155 farrowings were evaluated with sire model. The heritability (h2) of the evaluated traits was as follows: live born piglets 0.13, dead born piglets 0.07, litter weight at born 0.20, average weight at born 0.27, mortality in the first 21 days 0.11, 21 days piglets 0.09, litter weight at 21st day 0.12, average weight at 21st day 0.06, weaned piglets 0.08. Between the breeding values of the sires in estimated traits remarkable differences was found. The distance of the extreme values was 28.11 kg in the litter weight at 21st day, that is - know the price of the weaned piglets - not irrelevant difference. In evaluated traits was found stagnant genetic trends. An exception are the number of live born piglets (in a small compass increase), and the mortality in the first 21 days (in a small compass decrease).